(untitled) (The Peerian Journal, 2024)
Thrombophilias are still one of the pressing problems in obstetric practice.The last decade of the 20th century was marked by the discovery of a large number of genetically determined and acquired thrombophilias, which repeatedly increase the risk of thrombosis and thromboembolism during pregnancy.Currently, there is no doubt that thrombosis is one of the main causes of fatal outcomes in the world. Many researchers indicate that for every 1000 births there are 2-5 cases of thrombotic complications [1, 2]. Up to 50% of venous thromboses occur in patients under 40 years of age and are usually associated with pregnancy. Some authors note that the risk of venous thromboembolic complications in pregnant women is 4-10 times higher than in non-pregnant women of the same age. The risk increases with the onset of pregnancy and becomes maximum in the postpartum period [16, 17].This may be due to the fact that all the classical components of Virchow’s triad are present even in uncomplicated pregnancy and labor. Blood flow velocity in the vessels of the lower extremities decreases by almost 50%, changes in the hemostasis system occur (which are primarily manifested in the tendency